التنمية السياحية ومردودها الاجتماعي والاقتصادي في السودان - أحمد، أحمد آدم خليل; خيري، أمير حسن عبدالله محمد (جامعة أم درمان الإسلامية - كلية التربية, 2022)
تهدف التنمية السياحية إلى تحقيق منظومة متكاملة من الاستغلال الأمثل بين كافة العناصر الطبيعية والعناصر التراثية والحضارية بهدف تنمية مكونات المنتج السياحي لكي يجذب مستويات مختلفة من السائحين، وذلك من خلال الأخذ بمختلف البرامج والخطط التي تهدف إلى تحقق التنمية السياحية ذات مردود اجتماعي واقتصادي. يمكن صياغة مشكلة الدراسة؛ في توفر مقومات هائلة في مجال قطاع الترويح والترفيه والسياحة بالسودان، إلا أن مستوى ممارسة النشاط السياحي والمردود الاجتماعي والاقتصادي مازال دون مستوى الطموح. وتمثلت أهمية الدراسة؛ في الآثار المتنوعة والمتداخلة اجتماعيا واقتصاديا وبيئيا، بجانب أنها سانحة لتسليط الضوء على دولة السودان بإرثها وإنجازها الحضاري والتبصير بعطائها الإنساني. فضلا عن أهميتها كقطاع اقتصادي يساهم في زيادة الناتج المحلي الإجمالي. تجلت أهداف الدراسة؛ في السعي إلى التعرف على المقومات والإمكانيات الطبيعية والبشرية وتحديد الأنماط السياحية المتاحة، تقديم رؤية واقعية عن السياحة وإمكانية تنميتها وما يصاحبها من مشكلات بيئية، رصد وتحليل التغيرات الاقتصادية والاجتماعية للسكان. منهجية الدراسة؛ تمثلت في استخدام المنهج التاريخي، المنهج الوصفي التحليلي، والمنهج السلوكي، والأسلوب الكمي الإحصائي. توصلت الدراسة لعدة نتائج أهمها؛ تؤثر النواحي الدينية والاجتماعية والسياسية على السياحة. أبرزت السياحة الخصائص الثقافية للمجتمعات والشخصية السودانية للأخرين. يمكن لقطاع السياحة أن يوفر فرص عمل لنسبة (12%) من إجمالي العمالة. ساهم قطاع السياحة في زيادة الناتج المحلي الإجمالي بحوالي (68.3) مليون دولار. Aims of Tourism Development to achieve an integrated system of optimization between all natural elements and items of heritage and civilization with a view to the development of the components of the tourism product in order to attract different levels of tourists, through the introduction of various programmes and plans that aim to achieve tourism development-impact social and economic. Can formulate the problem of the study; the rectifiers provide tremendous in the field of recreation, leisure and tourism in Sudan, but that the level of activity of the tourism and socioeconomic impact are still without the level of ambition. The importance of the study; the effects of competing and overlapping socially, economically and environmentally, besides, it's an opportunity to shed light on the state of Sudan lady and its cultural justification even human. As well as its importance as a sector of the economy contributes to the increase of GDP. Reflected the objectives of attracting; in the quest to identify the ingredients and potential natural and human resources and identifying patterns of Tourism available, to provide a realistic vision for tourism and the possibility of its development and its attendant environmental problems, the monitoring and analysis of economic and social changes of the population. Methodology of the study; was to use the historic house, approach use analytical, and behavioral therapy, the method of quantitative statistical. The study has several findings, the most significant; affecting respects religious, social and political tourism. Highlighted tourism cultural characteristics of groups and the Sudanese to others. Can the tourism sector that provides job opportunities to the proportion (12%) of total employment. Contributed to the tourism sector in the GDP increase is estimated (68.3) million.
Keywords: التنمية الاقتصادية -- الاقتصاد السياحي -- التنمية السياحية -- الترويح السياحي